India Takes Slow Steps toward Internationalization - Pushkar, P (International Higher Education, 2019)
The Indian government and some universities have belatedly recognized the importance of internationalization and started to take measures to bring larger numbers of international students and faculty to Indian universities. While it seems unlikely that these first steps—such as the launch of the “Study in India” portal—will yield immediate results, India has finally taken the path of internationalization.